(untitled) (RT. A Journal on Research Policy and Evaluation, 2015)
Since the publication of Kitcher’s influential paper The Division of Cognitive Labor, some philosophers wondered about these two related issues: (1) which is the optimal distribution of cognitive efforts among rival methods within a scientific community?, and (2) whether and how can a community achieve such an optimal distribution? Though not committing to any specific answer to question (1), I claim that issue (2) does not depend exclusively on an invisible hand like mechanism, since both intra-scientific and extra-scientific institutions may play a major role. Finally, I examine some practical difficulties of reallocating scientists from a method to another, which leads to stress the importance of well-planned training and recruitment.